The improvement of the water treatment technology for the kvass production - Dulka, Olha; Prybylskyi, Vitalii; Oliynyk, Svitlana; Kuts, Anatoly; Kovalenko, O. (My University, 2019)
The composition of water significantly affect the flow of the process and the main indicators of the finished drink. The article presents the results of theoretical and experimental researches on improvement of the technology of preparation of drinking water for the production of non-alcoholic fermented beverages, in particular, bread kvass. The high efficiency of the application of natural minerals – clinoptilolite, rock crystal and activated carbon with combined treatment of water in the technology of bread kvass is proven. The quality and usefulness of the product depend on the content of its impurities. The integrated action of investigated materials with adsorption, ion exchange and redox properties provides water conditioning and achievement of the intensification of the technological process and high organoleptic qualities of the finished product. The work presents the physicalmechanical characteristics of the investigated materials, technological parameters of treatment, the influence of filter materials on the organoleptic and physical and chemical parameters of water and finished product. The article also gives a taste-aroma profile of bread kvass, made from the use of prepared water. The materials of the conducted research testify to the expediency of water treatment for the production of bread kvass in the sequence of clinoptilolite, active coal, rock crystal with a filtration rate of 8–15 m / h. In this case, the total iron content is reduced by 5 times, the total stiffness decreases by 75%, permanganate oxidation is 9 times. It has been established that such processing allows for high organoleptic qualities of prepared water and end product and increases the tasting score of bread kvass by 7 times, with no unpleasant taste and aroma that is characteristic of chlorinated water and decreases the turbidity of the beverage as a result of a decrease in the overall rigidity of water.На перебіг технологічного процесу та основні показники готового напою суттєво впливає склад води. У статті наведено результати теоретичних та експериментальних досліджень із удосконалення технології підготування питної води для виробництва хлібного квасу – найбільш поширеного безалкогольного ферментованого напою. Комплексна дія досліджуваних матеріалів із адсорбційними, іонообмінними та окисно-відновними властивостями забезпечує кондиціювання води та інтенсифікацію технологічного процесу, досягнення високих органолептичних якостей готового продукту. Від вмісту домішок води залежить якість та корисність готового продукту. Доведено високу ефективність застосування природних мінералів – клиноптилоліту та гірського кришталю, а також, активного вугілля при комбінованій обробці води в технології хлібного квасу. У роботі наведено фізико-механічні характеристики досліджуваних матеріалів, технологічні параметри обробки, вплив фільтрувальних матеріалів на фізико-хімічні та органолептичні показники води та готового продукту. У статті, також, наведено смако-ароматичний профіль хлібного квасу, виготовленого з використанням підготовленої води. Матеріали проведених досліджень свідчать про доцільність обробки води для виробництва хлібного квасу у послідовності клиноптилоліт, активне вугілля, гірський кришталь із швидкістю фільтрування 8–15 м/год. При цьому вміст загального заліза зменшується у 5 разів, загальна жорсткість знижується на 75%, перманганатна окиснюваність зменшується у 9 разів. Встановлено, що така обробка дозволяє надати високі органолептичні якості підготовленій воді та кінцевому продукту і збільшує дегустаційна оцінка хлібного квасу на 7 балів, при цьому відсутній неприємний смак та аромат, який характерний для хлорованої води та зменшується мутність напою внаслідок зниження загальної жорсткості води.
Keywords: bread kvass; mechanical filtration; water preparation; water; хлібний квас; механічне фільтрування; водопідготовка; вода; кафедра біотехнології продуктів бродіння і виноробства